Influence of socio-demographic and psychological factors on shaping farmers' pro-environmental behavior in Dinajpur, Bangladesh - Sarmin, Susmita; Hasan, Md. Faruq; Shahin, Atia (Asia-Pacific Journal of Regional Science, 2024)
Pro-environmental behavior (PEB) addresses environmental challenges such as climate change, pollution, habitat loss, and resource depletion. This research aimed to identify the most influential factors shaping farmers' pro-environmental behavior. The stud
Keywords: Environmental Citizenship; Psychological Factors; Social Environmentalism; Socio-Demographic Factors; Pro-Environmental Behavior